Meter and modernity in English verse, 1350-1650 - Weiskott, Eric (University of Pennsylvania Press, 2021)
Eric Weiskott examines the uses and misuses of three metrical forms as markers of literary periodization: alliterative meter, tetrameter, and pentameter. Rejecting the traditional division between medieval and modern, Weiskott's analysis of metrical history renegotiates the trajectories of English literary history between 1350 and 1650.
Keywords: English language -- Versification.; English poetry -- Middle English, 1100-1500 -- History and criticism.; English poetry -- Early modern, 1500-1700 -- History and criticism.; Poetics -- History.; English literature -- Periodization.; Anglais (Langue) -- Versification.; Poésie anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique.; Poétique -- Histoire.; LITERARY CRITICISM -- Medieval.; English language -- Versification; English literature -- Periodization; English poetry -- Early modern; English poetry -- Middle English; Poetics; 1100-1700; Cultural Studies.; Literature.; Criticism, interpretation, etc.; History; Literary criticism; Literary criticism.; Critiques littéraires.